2018
DOI: 10.1177/0010414018797954
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarian Institutions and Women’s Rights

Abstract: While dictatorships perform worse than democracies in respect for most human rights, a large number of autocracies have prioritized the advancement of women’s rights. We present a theory of authoritarian rights provision that focuses on the incentives for dictatorships to secure women’s loyalty, and we identify the particular capacity of institutionalized party-based regimes to supply—and capitalize from—women’s rights policies. Analyzing a comprehensive sample of authoritarian regimes from 1963 to 2009, we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 84 publications
0
64
0
1
Order By: Relevance
“…Cells are white and empty if there is no clear dominance relationship between two variables (i.e. if X>Y occurs in less than 50% of the cases) recent literature, we see women's rights (to discussion) develop comparatively earlier for cases ending in stabilised electoral authoritarianism (Donno and Kreft, 2019;Edgell, 2019). While beyond the scope of this paper, these exploratory results provide tentative directions for future research…”
Section: Methodsmentioning
confidence: 75%
“…Cells are white and empty if there is no clear dominance relationship between two variables (i.e. if X>Y occurs in less than 50% of the cases) recent literature, we see women's rights (to discussion) develop comparatively earlier for cases ending in stabilised electoral authoritarianism (Donno and Kreft, 2019;Edgell, 2019). While beyond the scope of this paper, these exploratory results provide tentative directions for future research…”
Section: Methodsmentioning
confidence: 75%
“…In cases such as Chad where political stability has been challenged by armed groups, repression of civil society including women's groups has occurred (Eizenga, 2018). Where repression has been less of a viable political option, there is a growing trend among dominant parties within sub-Saharan Africa to co-opt women's groups to promote more authoritarian political agendas (Donno and Kreft, 2019).…”
Section: Gender and Political Instabilitymentioning
confidence: 99%
“…Scholars have also connected democracy to improved women's rights (Lindberg, 2004), and found that democracies tend to out-perform autocracies when it comes to electing women to national office (Kang and Kim, 2018). However, recent research also suggests that authoritarian regimes have the incentive to coopt women, and use the provision of women's rights, including political rights and political representation, as a coalition building strategy (Donno and Kreft, 2018). A comparative case study of democratic Botswana and autocratic Rwanda suggests that democracy is not a necessary pre-condition for the adoption of gender quotas or having more women in parliament and that other factors may be more important in determining both outcomes (Bauer and Burnet, 2013).…”
Section: Formal Representation and Institutional Rulesmentioning
confidence: 99%